Digital Library in Education Administration Management - Sunu, I Gusti Ketut Arya (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
Digital libraries are a solution to the weaknesses of conventional libraries, because the characteristics of their collections are in digital form so as to provide convenience for users in terms of access that can be done anywhere and anytime. Digital libraries are currently experiencing a fairly good development. Its application is also found in various libraries, one of which is school libraries, both in junior and senior high schools. This study aims to analyze the effectiveness of digital libraries in the management of education administration in high school in terms of context, input, process, and product aspects. This research is an evaluation research with a quantitative approach. The population in this study is education staff. The sampling technique is done randomly. Data were collected using questionnaires, documentation and interviews. The steps for data analysis are as follows; 1) Change the raw score into a Z score (z-score), 2) Change the score of each CIPP variable into a T-Score, 3) Determine the direction of the T-Score for the Cotext, Input, Process and Product variables, 4) determine the direction of the T-Score score to the Glickman quadrant. The results obtained from the overall evaluation of the context, input, process, and product variables on the use of digital libraries, it was found that the effectiveness of using digital libraries was quite effective. The obstacles faced by digital libraries in managing education administration in high schools are the absence of a clear legal basis, vision, mission, goals, and also that digital library managers do not have academic qualifications according to their fields.